Contribution of Arm Muscle Power and Body Flexibility Regarding Volleyball Services for Athletes - Romadhonsyah, Achmad (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: The purpose of this research was to determine the contribution of arm muscle power and body flexibility to service for volleyball among athletes. Methodology: The type of this research is correlation. The sample in this study were 16 athletes. The research instrument used was an overhead medicine ball throw test, a sit and reach test and a service test for volleyball. The data analysis technique used is to calculate the value level of the relationship or multiple correlation Main Findings: Based on the results of data analysis, it is known that (1) There is a contribution of arm muscle power to service for volleyball for athletes of 38.81% with a value of rcount = 0.623> from the value of rtabel = 0.497, (2) There is a contribution of body flexibility to service for Volleyball for athletes is 42.90% with a value of rcount = 0.655> from the value of r table = 0.497, (3) There is a contribution of arm muscle power and body flexibility to service for volleyball for athletes of 51.55% with a value of rcount = 0.718 > from the value of rtabel = 0.497 Novelty/Originality of this study: The results of this research can provide new, more detailed insight into the importance of developing arm muscle strength and body flexibility in improving service quality, and can be used as a basis for designing more effective and specific training programs for athletes.